The Influence of Entrepreneurship on the Innovation Path of Cultural Enterprises Under the Background of Digital Transformation - Liu, Siting; Zhou, Yong; Wang, Changlin; Yu, Yufan (Frontiers in Psychology, 2022)
This study aims to explore the impact mechanism of the new dimension of entrepreneurship on the innovation performance of enterprises in the context of digital transformation. The relationship between entrepreneurship and enterprise innovation performance is studied in Beijing, Shanghai, Guangzhou, Shenzhen, and other high-tech enterprises represented by innovative companies. Firstly, the correlation hypothesis between variables is proposed through the induction and summary of relevant data and academic achievements. Statistical data is collected by means of a questionnaire survey. The content of the questionnaire includes three dimensions: 1. collective innovation, risk-taking, and integrity; 2. the survival performance and growth performance of new ventures; 3. basic information about the enterprise, such as the size, age, type, and classification of different Internet and the location. Statistical Product and Service Solutions (SPSS) and Advanced Mortar System (AMOS) statistical software are used to carry out statistical and correlation analyses of the valid questionnaires. Finally, the proposed hypothesis is verified through regression analysis. To sum up, the main conclusions are: the correlation coefficients between innovative spirit, adventurous spirit, integrity, and enterprise survival performance are 0.401, 0.426, and 0.393, respectively, which are positive correlations. The correlation coefficients between innovative spirit, adventurous spirit, integrity, and enterprise survival performance are 0.434, 0.367, and 0.536, respectively, and there is a significant and positive correlation. It shows that entrepreneurship and its three dimensions have a significant positive impact on enterprise entrepreneurial performance. The research examines the logical relationship and influence mechanism between the entrepreneurial spirit of entrepreneurs and the innovation performance of enterprises, which has a certain guiding role in the management practice of innovative enterprises in China.